(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
The orbitolinid foraminifer Dictyoconus arabicus Henson is described for the first time from the Tibetan plateau (Coqen-Gerze road, Lhasa block, Central Tibet). A discussion of the principal published data reveals that this species occurs in the Late Barremian, probably ranging to the Early Aptian. The intraspecific evolutionary degree of the studied specimens indicates a Late Barremian age. This dating leads to the conclusion that the Cretaceous marine ingression in the Lhasa block took place during the same time interval.